Overview of Nutritional Status Among Female Students - Ferdian, Dani; Hikmat, Rohman; Anshor, Abdullah; Irwan, Irwan; Triyanto, Triyanto (GLOBAL HEALTH SCIENCE GROUP, 2024)
The problem of nutritional imbalance in adolescent girls. Factors such as an unbalanced diet, low awareness of the importance of nutrition, and a sedentary lifestyle contribute to this nutritional problem. Poor nutritional status negatively impacts physical growth and development and mental health. Objective: to explore the nutritional status of students at SMA Plus Kopi Colol. Methods: The research method used was descriptive quantitative involving 51 female students as respondents. Data were collected through measurements of height, weight, abdominal circumference, and upper arm circumference. Data analysis was performed using descriptive statistics. Results: The results showed that all respondents were female. A small proportion of respondents had undernutrition as well as chronic energy deficiency. This shows that it is necessary to handle nutritional problems in female students at SMA Plus Kopi Colol. The participation of health workers and schools is needed to overcome nutritional problems in female students. Conclusion: More specific and targeted health intervention program planning related to nutritional status is needed to improve the health and well-being of SMA Plus Kopi Colol students.